Multi-objective optimization of energy, view, daylight and thermal comfort for building’s fenestration and shading system in hot-humid climates - Zhenling Wu; Yimin Xu; Zhuoyao Wang (PLoS ONE, 2025)
Well-designed building envelope components are essential in addressing global warming. Fenestration and shading system (F&SS) not only promote energy conservation and emission reduction but also enhance occupant satisfaction by improving indoor environments. However, existing research often prioritizes energy use, daylight, and thermal comfort while neglecting view quality, a factor closely tied to mental health and productivity. This study employs multi-objective optimization (MOO) to balance energy consumption, view quality, daylight, and thermal comfort in office buildings located in hot-humid climates. By optimizing variables such as window-to-wall ratio (WWR) and shading device dimensions, the research integrates random forest models with SHapley Additive exPlanations (SHAP) analysis to quantify the influence of design parameters on optimization goals. Results indicate maximum improvements of 25.62% in energy use intensity (EUI), 23.18% in thermal comfort percentage (TCP), and 37.96% in useful daylight illuminance (UDI), highlighting the substantial potential of the proposed framework. This research refines the MOO framework for F&SS design, offering new insights into view quality considerations. Recommended values, such as a WWR of 0.6, provide practical guidance for architects in balancing energy efficiency and occupant comfort.